1993
DOI: 10.1093/nar/21.22.5059
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic degradation of MAD3 (IϰBα) and enhanced processing of the NF-ϰB precursor p105 are obligatory steps in the activation of NF-ϰB

Abstract: We have studied the role of protein turnover in the induction of NF-kappa B DNA binding activity. Treatment of cells with tumour necrosis factor (TNF), double-stranded RNA (dsRNA), or phorbol esters is shown to be associated with an increase in the rate of p105 to p50 processing, and the loss of immunologically detectable MAD3/I kappa B alpha. Phosphate-labelling experiments indicate that these events are preceded by the phosphorylation of MAD3 and p105. The protease inhibitors TLCK (N alpha-p-Tosyl-L-Lysine C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
169
2

Year Published

1994
1994
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(184 citation statements)
references
References 56 publications
13
169
2
Order By: Relevance
“…Although dexamethasone alone has only a minor e ect on IkBa levels, the combination treatment results in a signi®cant increase in the total amount of IkBa protein ( Figure 4b). An identical result was obtained when the blots were probed with a previously described (Mellits et al, 1993) polyclonal antiserum raised against recombinant IkBa (data not shown). Stripping and reprobing the blot with an antibody to IkBb indicated that over the time scale of the experiment levels of this protein were not a ected by treatment with dexamethasone or ZLLLH (data not shown).…”
Section: Agents Which Allow Ikba To Accumulate Do Not In¯uence Nf-kb supporting
confidence: 80%
See 2 more Smart Citations
“…Although dexamethasone alone has only a minor e ect on IkBa levels, the combination treatment results in a signi®cant increase in the total amount of IkBa protein ( Figure 4b). An identical result was obtained when the blots were probed with a previously described (Mellits et al, 1993) polyclonal antiserum raised against recombinant IkBa (data not shown). Stripping and reprobing the blot with an antibody to IkBb indicated that over the time scale of the experiment levels of this protein were not a ected by treatment with dexamethasone or ZLLLH (data not shown).…”
Section: Agents Which Allow Ikba To Accumulate Do Not In¯uence Nf-kb supporting
confidence: 80%
“…IkBa was not detected in KM-H2 cells ( Figure 3). Identical results were obtained when a polyclonal antibody raised against recombinant IkBa (Mellits et al, 1993) (7) or supernatant from cells expressing CD40 ligand (+) for the indicated periods of time prior to preparation of cytoplasmic extracts. 25 mg of cytoplasmic extract was analysed by Western blotting using the 10B monoclonal antibody speci®c for IkBa (upper panels).…”
Section: Defective Ikba In Hodgkin Cell Linesmentioning
confidence: 69%
See 1 more Smart Citation
“…The antioxidant, PDTC, prevents de novo phosphorylation of I B␣ as well as its subsequent degradation via unknown primary cellular targets (30 -32). The protease inhibitor, TPCK, prevents the degradation of I B proteins (33,34). Both agents have been applied in numerous cell types to study NF-B-dependent events, suggesting that the observed block in the up-regulation of perforin in primary NK cells (Fig.…”
Section: Perforin Gene Regulation By Il-2 In Primary Nk Cells and Thementioning
confidence: 99%
“…TNF-a induces IkB-a phosphorylation (Beg et al, 1993;Henkel et al, 1993), yet this modification is not sufficient to trigger release of NF-kB and may be required for targeting IkB-a for subsequent proteolytic degradation (Alkalay et al, 1995;Beg et al, 1993;DiDonato et al, 1995;Finco et al, 1994;Finco and Baldwin, 1995;Henkel et al, 1993;Lin et al, 1995;Miyamoto et al, 1994;Traeckner et al, 1994). As some protease inhibitors can also block the induction of IkB-a phosphorylation, there may be a role for proteases prior to this step Mellits et al, 1993). Finally, in some cells, NF-kB activation by TNF-a is inhibited by antioxidants, suggesting that the signaling pathways leading to IkB-a degradation also involve ROS or redox-sensitive processes .…”
Section: Introductionmentioning
confidence: 99%